Parafilm-assisted microdissection: a sampling method for mass spectrometry-based identification of differentially expressed prostate cancer protein biomarkers. Issue 22 (9th December 2014) - Quanico, J.; Franck, J.; Gimeno, J. P.; Sabbagh, R.; Salzet, M.; Day, R.; Fournier, I.
Abstract : Profiling of tumors using a combined MALDI MS imaging and parafilm-assisted microdissection (PAM) workflow identified candidate biomarkers of prostate cancer. Abstract : Mass spectrometry-based methods for prostate cancer biomarker discovery are hampered by their low-throughput capabilities because of extensive sample preparation. We present the parafilm-assisted microdissection technique coupled with label-free quantification and bioinformatics analysis as a means to evaluate directly protein expression changes on benign and tumor regions.